The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10606-008-9077-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Digital Artifact-Mediated Coordination in Building Design

Abstract: We conducted an ethnographic field study examining how a building design team used representational artifacts to coordinate the design of building systems, structure, and architecture. The goals of this study were to characterize the different interactions meeting participants had with design artifacts, to identify bottlenecks in the design coordination process, and to develop design considerations for CSCW technology that will support in-person design coordination meetings of building design teams. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 54 publications
0
27
0
1
Order By: Relevance
“…In addition, the building design was developed and coordinated using a variety of BIM tools and collaboration technologies. Several students were actively engaged in this project and studied this project from a variety of perspectives: (1) one MASc student studied the coordination process, investigating how time is spent in meetings and the design artifacts used, and identifying the requirements for interactive workspaces [11], (2) another student identified and characterized the bottlenecks encountered in different meeting environments [12], and (3) another student worked with computer science students to characterize the interactions with different design artifacts [13]. This example illustrates the rich learning environments that can be created by working closely with industry practitioners.…”
Section: Learning From Practice a British Columbia Experiencementioning
confidence: 99%
“…In addition, the building design was developed and coordinated using a variety of BIM tools and collaboration technologies. Several students were actively engaged in this project and studied this project from a variety of perspectives: (1) one MASc student studied the coordination process, investigating how time is spent in meetings and the design artifacts used, and identifying the requirements for interactive workspaces [11], (2) another student identified and characterized the bottlenecks encountered in different meeting environments [12], and (3) another student worked with computer science students to characterize the interactions with different design artifacts [13]. This example illustrates the rich learning environments that can be created by working closely with industry practitioners.…”
Section: Learning From Practice a British Columbia Experiencementioning
confidence: 99%
“…Some researchers have proved by user tests that gesturing, navigation, annotation and viewing are the four primary interactions with design artefacts in technical meeting (Tory et al, 2008). According to their studies, the form of the design information (2D vs. 3D, digital vs. physical) has minimal impact on gesture interactions, although navigation varies significantly with different representations.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In order for such repositories to be of practical use, construction professionals need to be able to rapidly retrieve and manipulate relevant information from the large and diverse collection of documents within project archives (Steed et al 2012;Strotgen and Gertz 2012;Tory et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, on several of the construction projects we have studied, design and construction teams used Autodesk Buzzsaw® (Buzzsaw 2014), a third-party application that is often used as a central repository for project information archiving, sharing and retrieval. Tory et al (2008) found that design and construction professionals using these existing tools had a difficult time searching and locating project files unless they were already familiar with the hierarchy structure and the name of the item they were searching for. Similarly, Demian and Fruchter (2006a) reported that construction professionals often asked colleagues for information rather than searching project archives.…”
Section: Introductionmentioning
confidence: 99%